2015
DOI: 10.1021/acs.jpclett.5b00332
|View full text |Cite
|
Sign up to set email alerts
|

Role of LiCoO2 Surface Terminations in Oxygen Reduction and Evolution Kinetics

Abstract: Oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) activities of LiCoO2 nanorods with sizes in the range from 9 to 40 nm were studied in alkaline solution. The sides of these nanorods were terminated with low-index surfaces such as (003), while the tips were terminated largely with high-index surfaces such as (104), as revealed by high-resolution transmission electron microscopy. Electron energy loss spectroscopy demonstrated that low-spin Co(3+) prevailed on the sides, while the tips exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
60
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 31 publications
8
60
0
Order By: Relevance
“…It can be seen that MnCo 2 O 4 spinels locate at the left branch of the OER volcano plot, which confirms our previous explanation on the linear dependence in Figure b. This theory also explains the recent observation on Li 2 Co 2 O 4 ,[7c,34] where the switch in spin state from Co 3+ (normalt2g6normalenormalg0, low spin) to Co 3+ (normalt2g6xnormalenormalgx, x ≈ 1, intermediate spin) at the octahedral site gives drastically enhanced ORR/OER activity. Note that our principle is different from the e g theory in perovskites, where there is only one geometric site.…”
supporting
confidence: 90%
“…It can be seen that MnCo 2 O 4 spinels locate at the left branch of the OER volcano plot, which confirms our previous explanation on the linear dependence in Figure b. This theory also explains the recent observation on Li 2 Co 2 O 4 ,[7c,34] where the switch in spin state from Co 3+ (normalt2g6normalenormalg0, low spin) to Co 3+ (normalt2g6xnormalenormalgx, x ≈ 1, intermediate spin) at the octahedral site gives drastically enhanced ORR/OER activity. Note that our principle is different from the e g theory in perovskites, where there is only one geometric site.…”
supporting
confidence: 90%
“…Analogously, a very recent study on LiCoO 2 for electrochemical water oxidation and oxygen reduction also revealed the impact of charge transfer processes on the catalytic activity. 16b, 32 The water oxidation activity of various catalyst types, such as perovskites and lithium battery materials, was generally perceived to be strongly influenced by their surface states. However, recent studies also showed that the activities of two representative materials may still be different, regardless of the formation of virtually identical Co-Pi layers on their surface under electrochemical water oxidation conditions.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[9,[70][71][72] The studied catalysts Ni MOF and NiO WCP in this article are associated with a q* value of 1156 and 875 mC cm À2 mg À1 respectively. E 1 and E 2 are the range of scanned voltage used for the measurement of q*.…”
Section: Physical and Chemical Characterizationsmentioning
confidence: 99%